Conceptual Model for Effective Implementation of Industrial Symbiosis: A Case Study of Mab-Ta-Phut Industrial Estate - Termsinvanich, Paitoon; Thadaniti, Suwattana; Wiwattanadate, Dawan (Mediterranean Journal of Social Sciences, 2013)
This paper illustrates effective factors as well as a model for effective implementation of industrial symbiosis (IS) in Mab-Ta-Phut Industrial Estate that was used (MTBIE) as a case study. The study was carried out using questionnaires, in-depthinterview, and site survey both factories in MTBIE and waste processor plants in Saraburi Province. Information from the studyindicates that policy (on zero discharge, zero waste to landfill and willingness to adjust process), initiator, information (on wastegeneration), and financial mechanisms are effective factors influencing IS implementation, while technology and publicparticipation are not as effective for the case of factories in the industrial estate. Therefore, a model for effectiveimplementation of industrial symbiosis in industrial estate is proposed and presented in this paper.